Moderating role of managerial optimism on the relationship between macroeconomic uncertainty and capital structure decisions - Chow, Yee Peng; Muhammad, Junaina; Ariffin, A.N. Bany; Cheng, Fan Fah (Inderscience Publishers, 2024)
This paper investigates the moderating role of managerial optimism on the association between macroeconomic uncertainty and capital structure decisions. Drawing on a panel of 907 listed non-financial firms from seven Asia-Pacific countries over the period 2004 to 2020, this paper estimates the regression models using the system generalised method of moments technique. The results provide evidence of the negative influence of macroeconomic uncertainty on leverage. However, in contrast to the common belief that managerial optimism encourages more leverage, this paper finds that when managerial optimism is interacted with macroeconomic uncertainty, the former fails to mitigate the initial negative effect of the latter on leverage. Further analyses on the individual measures of managerial optimism demonstrate that only the gender of the CEO or chair of the board weakens this negative relationship, while the CEO's or chair's founder status, excessive shareholdings and monetary value invested in the firm's common shares strengthen this relationship.